Effect To Loving Touch Baby Massage In Increasing The Frequency Of Breastfeeding - Handajani, Diani Octaviyanti; Suprapti, Suprapti; Rahayu, Ria Muji; Mulyani, Endah; Sulastri, Sulastri (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
Breastfeeding is very important in Growth and development of children both physically and mentally optimally and improve children's intelligence, and prevent children from diseases such as diarrhea, pneumonia and malnutrition which are common causes of death in children under 5 years. In breastfeeding, many factors influence, one of which is giving with loving touch baby massage. Giving with loving touch baby massage is expected to affect the frequency of breastfeeding and can increase the closeness of the child to the parents (Bonding). This research is a quasi-experimental research, namely research that aims to determine the effect that will arise after being given treatment, namely baby massage. The population in this study were 30 children under five in Domas Village, Gresik Regency. The independent variable in this study was loving touch baby massage, the dependent variable was the frequency of breastfeeding. The statistical test used was the Paired Sample T-Test. The results of this study can be concluded that there is an effect of baby massage on the frequency of breastfeeding and has a frequency of breastfeeding 7 times - 10 times / day greater than babies who are not done loving touch baby massage.